Delayed graft function and perfusion parameters of kidneys from uncontrolled donors after circulatory death. (April 2021) - Peris, Adriano; Fulceri, Giorgio Enzo; Lazzeri, Chiara; Bonizzoli, Manuela; Li Marzi, Vincenzo; Serni, Sergio; Cirami, Lino; Migliaccio, Maria Luisa
Better preservation and evaluation of kidneys from donors after circulatory death serve to increase the number of kidneys available for transplantation and hypothermic machine perfusion has been shown to decrease ischemia reperfusion injury and delayed graft function. Data on relation between hemodynamic parameters during hypothermic machine perfusion and delayed graft function in kidneys from donors after circulatory death are so far scarce and not univocal. We aimed at assessing whether hemodynamic parameters measured during hypothermic machine perfusion (flow, mean perfusion pressure, and renal resistance) are associated with delayed graft function in 26 kidneys retrieved from uncontrolled donors after circulatory death. In our series, the incidence of delayed graft function was 57.7% (15/26). Recipients who developed delayed graft function had a longer warm ischemic time (p = 0.04). All hemodynamic parameters measured during hypothermic machine perfusion were comparable between recipients with delayed graft function and those without. According to our data, in kidneys from uncontrolled donors after circulatory death, a longer warm ischemic time (that is the overall time of no flow, as the sum of the no-flow and the no-touch period) is associated with delayed graft function. This finding underscores the pivotal role of ischemic injury in terms of absence of flow in affecting graft function. No association was detectable between hemodynamic parameters during hypothermic machine perfusion and the development of delayed graft function in our series.